Correlates of Academic Overachievement, Nondiscrepant Achievement, and Learning Disability in ADHD, Autism, and General Population Samples. Issue 1 (1st January 2020) - Mayes, Susan Dickerson; Waschbusch, Daniel A.; Calhoun, Susan L.; Mattison, Richard E.
ABSTRACT: Little is known about the characteristics of academic overachievers, children whose achievement significantly exceeds IQ. Correlates of overachievement (achievement test scores ≥ 1 SD above IQ), nondiscrepant achievement, and learning disability (LD; achievement ≥ 1 SD below IQ) were analyzed in 1, 543 children (739 ADHD, 285 autism, and 519 general population), 6–16 years of age. Significant correlates of the reading and math achievement groups were diagnosis (autism greatest overachievement, ADHD greatest LD), IQ (lowest in overachievers and highest in LD), and Working Memory scores relative to the child's IQ (close to or exceeding IQ in overachievers and lower than IQ in LD). Demographics (age, sex, race, and parent occupation) and parent and teacher ratings of psychopathology (e.g., behavior problems, anxiety, and depression) and personality characteristics (e.g., motivation and self-confidence) did not contribute significantly more to predicting overachievement and LD beyond that explained by IQ, diagnosis, and working memory. These findings suggest an underlying neurobiological etiology for both overachievement and LD.